Lifestyle as a Predictor of Socio-Economic Status in Retirement: Evidence from Pensioners from the Busoga Sub-Region, Uganda - Fabian, Mwosi; Charles, Edaku; Robina, Mirembe; Eton, Marus (Society & Sustainability, 2022)
Most studies on retirement planning focus on preserving money and accumulating wealth and ignore the lifestyles of individual employees. This study promotes a discussion on lifestyle as a predictor of socio-economic status in retirement. Based on 236 pensioners from the Busoga sub-region, we used ‘the way of living’ to indicate lifestyle. We used household expenditure, access to healthcare, and housing quality to indicate socio-economic status. We used descriptive measures to report on lifestyle and Spearman’s correlation coefficient to document the relationship between workers’ lifestyle and socio-economic status in retirement. Strong attachments to family and intimate relations during one’s working life predict a satisfying retirement life. Civil servants who avoid harmful substances and exercise regularly are likely to retire in good health. There is a moderate and significant association between lifestyle and socio-economic status among civil servants in Uganda. Supervisors and human resource officers in government agencies and departments should conduct regular workshops to help government workers build strong attachments to their families, friends, social groups, and communities. We provide a solid foundation for working individuals to always reflect on the quality of their relations with their families, friends, social groups, and communities. This study contributes to the retirement planning research by shifting the focus to lifestyle, arguing that all forms of saving and financial planning for the future hinge on an individual worker’s lifestyle.